ECONOMIC ANOMALIES: AN ANALYSIS OF CONCERT TICKET PURCHASE TRENDS IN THE MIDST OF DEFLATION IN INDONESIA - Nurhayati, Dwi Astuti Wahyu; Oktavia, Novi Tri (JURNAL DIMENSI, 2024)
This study aims to analyze the phenomenon of economic anomalies seen in the trend of concert ticket purchases in Indonesia despite being in the midst of deflationary conditions that take place consecutively from May to September 2024. Although people's purchasing power has decreased due to the decline in the price of goods and services, as well as the existence of symptoms of economic sluggishness, interest in music concerts from both local and international musicians continues to increase. This phenomenon has attracted the attention of researchers because it indicates a change in people's consumption patterns who prefer spending on entertainment over basic needs. This study uses a qualitative approach with in-depth interviews with a number of concert ticket consumers in various major cities in Indonesia, and field observations to understand consumer behavior in this context, as well as documentation in the form of analysis of news articles, social media, concert reviews, and economic reports. The data analysis techniques used are data condensation, data presentation, conclusion drawing and NVivo12 verification. The results of the study show that the purchase of concert tickets is more influenced by emotional needs and self-reward Although the economy is sluggish, entertainment is considered a priority by some people, leading to a change in consumption patterns that focus more on social experiences and long-term memories.